Al3+/Ag1+ induced phase transformation of MnO2 nanoparticles from α to β and their enhanced electrical and photocatalytic properties. Issue 7 (May 2020) - Khalid, Muhammad Usman; Warsi, Muhammad Farooq; Shakir, Imran; Aly Aboud, Mohamed F.; Shahid, Muhammad; Shar, Sahar Saad; Zulfiqar, Sonia
Abstract: MnO2 is found in different crystal phases and morphologies depending upon the linkage of basic octahedral units [MnO6 ]. Here in this article, the MnO2 nanoparticles with pure α-phase, mixed α + β-phase and β-phase were prepared via wet redox method. Structural analysis of all prepared MnO2 based nanoparticles was done using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopic studies. XRD analysis revealed the phase transformation from α to β phase of MnO2 as a function of dopant. XRD data was also used to determine other structural parameters, crystallite size etc. The crystallite size was found <20 nm. UV–visible spectroscopy revealed that Al doped MnO2 showed better absorption than all other compositions towards visible region. The optical bandgap was calculated using Tauc plot from UV/Visible spectra of aqueous dispersions of MnO2 nanoparticles. The range of optical bandgap was found 2.06–2.52 eV. Effect of doing and co-doping on structural, optical and electrical parameters of MnO2 has been investigated and discussed. The DC electrical properties were studied using two probe technique and a significant effect of dopants has been observed on the electrical properties. The potential application (photocatalytic) studies of the undoped MnO2 and Al-doped MnO2 were also investigated. Methylene blue was used as typical organic compound. The Al-doped MnO2 nanoparticles exhibited the better photocatalytic efficiency as compared to pure MnO2 nanoparticles.